Behavioral sport psychology evidence-based approaches to performance enhancement - Luiselli, Jam.; Reed, Der.; SpringerLink (Online ser. (New York Springer, 2011)
Behavioral Sport Psychology Evidence-Based Approaches to Performance Enhancement   James K. Luiselli and Derek D. Reed, editors     From its fringe beginnings in the 1960s, sport psychology has evolved into a mainstream specialty, encompassing motivation, confidence building, error reduction, and self-help tools, among others. Whether the athletes involved play for pro teams, are still in school, or are weekend warriors, performance enhancement?an area highly subject to rumor, conjecture, and guesswork?is at the core of these applications.   Behavioral Sport Psychology replaces hunches and the grapevine with solid science useful to both veteran and novice professionals in the field. Starting with an overview of key aspects of the discipline, this volume distills the essentials of performance enhancement research and practice, pinpointing behavioral strategies that produce better outcomes and explaining their efficiency. Chapters examine issues associated with measurement techniques (including cognitive assessment, sabermetrics, and actigraphy), and bedrock topics such as aggression management, behavioral momentum, and coach training are treated in depth. Authoritative discussion of ongoing controversies and emerging areas of interest makes the book particularly accessible and up to date. Featured in the coverage:   The quantitative analysis of sports. Cognitive-behavioral performance enhancement strategies. Single-case evaluation of behavioral coaching interventions. Goal-setting and performance feedback. Behavioral effects of sport nutritional supplements: fact or fiction? Sport neuropsychology and concussions.   A lucid source of effective interventions, and of the evidence behind them, Behavioral Sport Psychology merits a wide audience among academic and non-academic professionals, practitioners, and consultants at every level of sports psycho
Preface -- Introduction -- Overview of Behavioral Sport Psychology -- Assessment and Measurement -- Measurement of Physical Activity -- Quantitative Analysis -- Single-Case Evaluation of Behavioral Coaching Interventions -- Cognitive Assessment in Behavioral Sport Psychology -- Performance Enhancement -- Goal Setting and Performance Feedback -- Positive Reinforcement and Incentive Systems -- Cognitive-Behavioral Strategies -- Increasing and Maintaining Physical Exercise -- Behavioral Momentum -- Special Topics -- Behavioral Consultation in Coaching -- Brain Injury Prevention -- Supporting Youth Participation in Sports -- Behavioral Effects of Sport Nutritional Supplements: Fact or Fiction? -- Behavioral Sport Psychology with Elite Athletes.
Electronic reproduction.
Keywords: Sports -- Psychological asp; Electronic book